2022
DOI: 10.1097/mpa.0000000000002100
|View full text |Cite
|
Sign up to set email alerts
|

Well-Differentiated Grade 3 Neuroendocrine Tumors

Abstract: Objectives:We evaluated a population-based cohort of metastatic welldifferentiated grade 3 gastroenteropancreatic neuroendocrine tumors (G3 NETs) to describe their characteristics, prognosis, and treatment outcomes. Methods:The British Columbia provincial database was queried for G3 NETs diagnosed 2004 to 2021, and charts were reviewed to describe clinical features and outcomes.Results: Forty-one patients were identified, most were diagnosed with pancreatic (58.5%) or midgut (26.8%) primary tumor and Ki-67 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In all, 29 studies met the predefined inclusion criteria, totaling 2955 NET patients, of which 25.8% (761 patients; range: 5–74) had G3 GEP or unknown primary G3 NET origins. 4 , 12 – 39…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In all, 29 studies met the predefined inclusion criteria, totaling 2955 NET patients, of which 25.8% (761 patients; range: 5–74) had G3 GEP or unknown primary G3 NET origins. 4 , 12 – 39…”
Section: Resultsmentioning
confidence: 99%
“…Pathology review was performed in 23 studies (79.3%). 10 , 12 14 , 16 , 18 , 20 27 , 29 , 31 36 , 38 , 39 As shown in Table 3 , the Ki-67 index was described in 15 studies, and the median values ranged from 23% to 61%; p53 immunohistochemistry (IHC) expression and/or TP53 mutation status was evaluated in six studies, with mutation or hyperexpression present in 0% to 21%; DAXX/ATRX and MEN1 mutation status were described in three studies, and were found in 0–25% and 0–21% of the patients, respectively, mostly in pancreatic NET.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations